Inducible displacement CT increases the diagnostic accuracy of aseptic loosening in primary total hip arthroplasty. - SANDBERG, Olof; CARLSSON, Sofia; HARBOM, Ellen; CAPPELEN, Vendela; THOLÉN, Simon; OLIVECRONA, Henrik; WRETENBERG, Per (Acta Orthopaedica, 2022)
Background and purpose -- Inducible displacement CT compares 2 CTs acquired in series but with alternated rotation of the femur. This provides visual and quantitative clues as to the mechanical situation, i.e., loosening, of a total hip arthroplasty. We report the accuracy of this method as well as the experience of integrating it into a clinical workflow. Patients and methods -- This was a retrospective single centre study of 72 cases of suspected aseptic loosening were the surgeon after reviewing a standard plain radiograph saw a need for more information. The displacement CT and plain radiograph were compared either to intraoperative findings or a 1--3 year follow up questionnaire for patients that did not have revision surgery. Patients reporting degradation in status since the time of the displacement CT were called for a follow up plain radiograph. Sensitivity and specificity were assessed, and user experience gathered. Results -- Of 72 enrolled patients 15 were lost to followup. Of the remaining 57, 17 were judged by in-traoperative findings or follow-up to have had loose implants. For plain radiography the sensitivity and specificity were 59% (95% CI 35--82) and 85% (74--96). For displacement CT the corresponding values were 77% (56--97), and 100% (100--100) respectively. The tool was adaptable to clinical routine. Conclusion -- Displacement CT with alternated rotations of the femur is a viable option to improve the diagnostic process for identifying aseptic loosening in a total hip arthroplasty.